History of Romanians for the baccalaureate exams, year 1941 (Confluenţe Bibliologice, 2023)
The article presents information about professor Pamfil Georgian's textbook ,,History of Romanians for Baccalaureate Exams", a volume published for the first time in 1929.
Keywords: Romanian history; baccalaureate